Providing a paediatric trauma and orthopaedics service during the peak of the COVID-19 pandemic: The Royal National Orthopaedic Hospital experience. (19th June 2020) - Iliadis, Alexis D; Eastwood, Deborah M; Bayliss, Lee; Cooper, Michael; Gibson, Alexander; Hargunani, Rikin; Calder, Peter; ,
Abstract : Introduction: In response to the COVID-19 pandemic, there was a rapidly implemented restructuring of UK healthcare services. The The Royal National Orthopaedic Hospital, Stanmore, became a central hub for the provision of trauma services for North Central/East London (NCEL) while providing a musculoskeletal tumour service for the south of England, the Midlands, and Wales and an urgent spinal service for London. This study reviews our paediatric practice over this period in order to share our experience and lessons learned. Our hospital admission pathways are described and the safety of surgical and interventional radiological procedures performed under general anaesthesia (GA) with regards to COVID-19 in a paediatric population are evaluated. Methods: All paediatric patients (≤ 16 years) treated in our institution during the six-week peak period of the pandemic were included. Prospective data for all paediatric trauma and urgent elective admissions and retrospective data for all sarcoma admissions were collected. Telephone interviews were conducted with all patients and families to assess COVID-19 related morbidity at 14 days post-discharge. Results: Overall, 100 children underwent surgery or interventional radiological procedures under GA between 20 March and 8 May 2020. There were 35 trauma cases, 20 urgent elective orthopaedic cases, two spinal emergency cases, 25 admissions for interventional radiology procedures, and 18 tumour cases. 78% of trauma cases were performed within 24 hours of referral. In the 97% who responded at two weeks following discharge, there were no cases of symptomatic COVID-19 in any patient or member of their households. Conclusion: Despite the extensive restructuring of services and the widespread concerns over the surgical and anaesthetic management of paediatric patients during this period, we treated 100 asymptomatic patients across different orthopaedic subspecialties without apparent COVID-19 or unexpected respiratory complications in the early postoperative period. The data provides assurance for health care professionals and families and informs the consenting process. Cite this article: Bone Joint Open 2020;1-6:287–292.